Asymptomatic Bone Marrow Edema in Weight-bearing Bones in Athletes and Military Trainees: A Systematic Literature Review - Karimi, Amir; El-Abtah, Mohamed; Sinkler, Margaret; Faraji, Navid; Voos, James; Harlow, Ethan; Miskovsky, Shana (International Journal of Sports Medicine, 2023)
Asymptomatic bone marrow edema (aBME) is a non-specific radiographic finding often found in athletes. Although aBME may represent the body's physiological response to training load, the etiology, MRI characteristics, and natural history of aBME remain unknown. To better characterize aBME in the lower extremities of military trainees and athletes. A systematic literature review in accordance with PRISMA guidelines was performed to identify primary research articles reporting on aBME in the lower extremities of athletes and military trainees. We identified 347 unique articles and after applying inclusion and exclusion criteria, 10 articles were included for qualitative synthesis. There were a total of 444 patients with an average age of 28.4±9.6 included. The most commonly used MRI sequences were proton-density with fat-saturation and T1-weighted imaging. The pattern of BME was inconsistently described, with various classification schemas used. The changes in aBME during longitudinal follow-up were dynamic and demonstrated both radiographic progression and regression. aBME is a highly prevalent and radiographically dynamic entity observed in high-level athletes and military trainees. Although follow-up was limited in the included studies, aBME may represent a natural, non-pathologic, reaction in response to specific biomechanical stressors.
Keywords: bone marrow edema; athletes; military; military recruits; aBME; asymptomatic